GENOTYPE × ENVIRONMENT INTERACTION AND HERITABILITY ESTIMATES FOR SOME AGRONOMIC CHARACTERS IN SUNFLOWER - H. Khan; H. U. Rehman; J. Bakht; S. A. Khan; I. Hussain; A. Khan; S. Ali (Journal of Animal and Plant Sciences, 2013)
This study was conducted at two locations over two years to determine the extent of genotype by environment (GE) interaction and heritability estimates for 35 sunflower genotypes including 10 parents (five each cytoplasmic male sterile lines and restorers/male and their 25 crosses). The traits studied were plant height, leaf area, stem girth, head diameter, seed and oil yield. The combined analysis of variance across years and locations revealed highly significant differences among the genotypes for all traits. A significant GLY interaction was observed for all traits except plant height. The GL interaction was also significant for all traits except stem girth. The GY interaction was found non-significant for all six traits. GY (σ²GY) variance was found largest for plant height (678.27) and leaf area (2483.86). Variance due to genotypes (σ²G) was found largest for stem girth (0.19), head diameter (6.60), seed yield (199303.97) and oil yield (46621.56). GLY (σ²GLY) variance was largest for stem girth. On entry mean basis very high estimates of heritability were observed for head diameter and oil yield (0.86±0.22) followed by seed yield and leaf area (0.85±0.24) and stem girth (0.84±0.22). Plant height was found to be a low heritable trait (0.30±0.10). Plant height was greatly influenced by the diversity in both locations and therefore, testing of genotypes over a wide range of locations is suggested to increase heritability.
Keywords: Genotype; environment; heritability; sunflower